Interpretações sobre a burguesia industrial brasileira: um breve balanço - Barbosa, Agnaldo de Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2003)
Neste artigo pretendemos realizar um breve balanço das principais correntes interpretativas que buscaram compreender e explicar o “comportamento” e a “mentalidade” da burguesia nas décadas que marcaram a sua origem e posterior consolidação.

In this article we intend to make a brief critical record of the main interpretative trends that tried to understand and explain the “behavior” and the “mentality” of the Brazilian industrial bourgeoisie in the decades that determined its origin and subsequent consolidation.
The Brazilian industrial bourgeoisie: a brief critical record
Keywords: Industrial bourgeoisie; Brazilian capitalism; Hegemony; Burguesia industrial; Capitalismo brasileiro; Hegemonia